(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The article begins with an overview of Uzbekistan’s historical significance, emphasizing its role as a vital hub along the ancient Silk Road trade route.Samarkand: Detailed description of Samarkand’s prominence as one of the oldest inhabited cities in Central Asia.